Hypothyroidism and Adverse Endpoints in Diabetic Patients: A Systematic Review and Meta-Analysis - Zhang, Shaojun; Feng, Guilong; Kang, Fangfang; Guo, Yali; Ti, Hongyan; Hao, Lufang; Gao, Peng; Gao, Jiangqin (Frontiers in Endocrinology, 2020)
Background: This study investigated the relationship strength between hypothyroidism and cardiovascular and renal outcomes in diabetic patients. Methods: The electronic databases PubMed, EmBase, and Cochrane library were screened for relevant studies published before November 2018. The outcomes included major cardiovascular events (MACEs), all-cause mortality, cardiac death, stroke, diabetic nephropathy (DN), diabetic retinopathy (DR), and chronic kidney disease (CKD). The pooled results for all outcomes were calculated using random-effects models. Results: A total of eight studies met the inclusion criteria. The summary results indicated that hypothyroidism was not associated with the risk of MACEs (OR:1.21; 95%CI:0.68-2.16; P=0.514), all-cause mortality (OR:1.27; 95%CI:0.93-1.74; P=0.136), cardiac death (OR:1.16; 95%CI:0.89-1.52; P=0.271), stroke (OR:0.96; 95%CI: 0.49-1.88; P=0.915), and DN (OR:1.71; 95%CI:0.37-7.90; P=0.490). There was a significant association between hypothyroidism and the risk of DR (OR:1.73; 95%CI:1.08-2.77; P=0.023) and CKD (OR:1.22; 95%CI:1.10-1.36; P<0.001). Conclusions: These findings indicate that diabetic patients with hypothyroidism have an increased risk of DR and CKD. Additional large-scale prospective studies should be carried out to verify the prognosis of patients with diabetes and hypothyroidism.